SOCIAL NEUROSIS IN CARDIOLOGICAL PRACTICE - Е. О. Taratukhin (Российский кардиологический журнал)
In the article, an original meaning is proposed for the term “social neurosis”, developed during transdisciplinary research. In the analysis, recent literature was included, on psychosomatic relations in pathogenesis of myocardial infarction, and the results of empirical study (interviews, questionnaires) in myocardial infarction setting. As “social neurosis”, psychosomatic condition should be meant, that is determined by experiencing of social and cultural life with following shifts in neurohumoral reactions that are bidirectionally linked to the phenomenal Self. As the phenomenal, the living through is understood, of the human as conscious, selfidentifying, thinking and emotioning subject. Practically oriented concept, “social neurosis”, being a generalizing term, might be useful for description of the cultural and social influences that lead to undercoping, chronic experiencing of negative socially oriented emotions, self-destructive behavior. Also, the meaning “somatized social neurosis” is presented that is related to the biomedical part of the problem.